PELUANG DAN TANTANGAN GURU DALAM MENGHADAPI ERA DIGITAL - Nur Al Fatah; Amirudin Amirudin (Lembaga Publikasi Ilmiah, 2022)
The speed of information flow that allows children to know something faster than what is obtained in school. In fact, there may even be many things that can be known that actually isn't time to know, they get information from Google. The speed of information as a result of advances in information technology will affect the pattern of human life in general and especially for the world of education, especially teachers. In the current era of information technology advancements that are not limited by space and time, it can enable student-centered learning strategies, encourage students to learn creatively and independently, prepare for global competition. E-learning based learning provides its own advantages in a learning culture. Educators (teachers) must be able to develop knowledge and skills, facilitate learning, understand learning and the things needed in learning. Advances in information technology provide great opportunities and challenges for teachers to continue to improve their competencies. Teacher competence as a whole consists of pedagogic competence, personality competence, social competence and professional competence must continue to be leveled to be able to answer today's global challenges. Several efforts must be made in dealing with the challenges of educators in this millennial era, including teachers should not stutter in technology, understand trends that occur related to changes in information technology. ABSTRAK Kecepatan arus informasi yang sangat memungkinkan anak mengetahui sesuatu lebih cepat dari apa yang didapat dibangku sekolah. Bahkan mungkin pula ada banyak hal yang dapat diketahui yang sebenarnya belum waktunya untuk diketahui, mereka mendapatkan informasi dari Google. Kecepatan informasi sebagai akibat kemajuan teknologi informasi tersebut akan mempengaruhi pola kehidupan manusia pada umumnya dan khususnya bagi dunia pendidikan khususnya guru. Di era kemajuan teknologi informasi yang tidak terbatas ruang dan waktu seperti sekarang ini, dapat memungkinkan strategi belajar berpusat kepada siswa, mendorong siswa belajar kreatif dan mandiri, bersiap dalam persaingan global. Pembelajaran berbasis e-learning memberikan keuntungan tersendiri dalam budaya belajar. Pendidik (Guru) harus mampu mengembangkan pengetahuan dan keterampilan, memfasilitasi pembelajaran, memahami belajar dan hal hal yang dibutuhkan dalam pembelajaran. Kemajuan teknologi informasi memberikan peluang dan tantangan yang begitu besar bagi guru untuk terus meningkatkan kompetensinya. Kompetensi guru secara utuh terdiri dari kompetensi pedagogic, kompetensi kepribadian, kompetensi social dan kompetensi keprofesionalan harus terus ditingkatan untuk dapat menjawab tantangan global saat ini. Beberapa upaya yang harus dilakukan dalam menghapi tantangan pendidik di era milenial ini yaitu diantaranya guru tidak boleh gagap teknologi, memahami kecenderungan yang terjadi terkait perubahan teknologi informasi.